The Role of Power Elites on Rural Transformation in Gombe State: An Assessment of Kashere Town - Abdullahi, Ibrahim; Ali, Jamila; Musa, Umar Farouk (Kashere Journal of Politics and International Relations, 2023)
This study investigated the role of power elites in rural transformation in Nigeria with specific reference to Gombe State in which Kashere Town (2003-2011) is taken as area of study. The study assessed the level of impact of political office holders in transforming of Kashere. The study utilized primary source in which questionnaires were administered. The data obtained were presented and analysed using chi-square statistics and the hypotheses developed were tested with the aid of Statistical Package for the Social Sciences (SPSS version 16.0). Elite theory was adopted as a framework of analysis. The study discovered that, Power Elite played a positive impact on the transformation of Kashere Town, The recommendations made are: Politicians in government (power) should introduce far reaching rural transformation agendas that aimed at improving the lives of rural inhabitants particularly those living in Kashere town. Politicians should also involve the beneficiaries of rural transformation right from the point of conception to implementation of projects. This will help reduce the vandalization and misconception by rural dwellers that rural development projects are government projects rather than their projects.